Infrared Laser Speckle Projection-Based Multi-Sensor Collaborative Human Body Automatic Scanning System - Xiao Yang (MDPI AG, 2021)
Human body scanning is an important means to build a digital 3D model of the human body, which is the basis for intelligent clothing production, human obesity analysis, and medical plastic surgery applications, etc. Comparing to commonly used optical scanning technologies such as laser scanning and fringe structured light, infrared laser speckle projection-based 3D scanning technology has the advantages of single-shot, simple control, and avoiding light stimulation to human eyes. In this paper, a multi-sensor collaborative digital human body scanning system based on near-infrared laser speckle projection is proposed, which occupies less than 2 m2 and has a scanning period of about 60 s. Additionally, the system calibration method and control scheme are proposed for the scanning system, and the serial-parallel computing strategy is developed based on the unified computing equipment architecture (CUDA), so as to realize the rapid calculation and automatic registration of local point cloud data. Finally, the effectiveness and time efficiency of the system are evaluated through anthropometric experiments.